Metode Extreme Programming Pada Sistem Informasi Penjualan Toko Berbasis Website - Nasir, Mochamad; Artanto, Fenilinas Adi; Hardani, Andaru Alwan Afif; Aini, Aulia Nurul (Journal of Information System Research (JOSH), 2025)
The development of a website-based information system has become an efficient solution for improving the sales and marketing process, especially for small businesses such as Toko Amuan which sells shirts. To address Toko Amuan's need for information system development, a website-based sales information system was created using the Extreme Programming (XP) development method and Unified Modeling Language (UML) design. This system has two main access rights, namely admin as shop manager and user as buyer or customer. Users have access to view products, place orders and complete payments. Meanwhile, the admin is tasked with managing products, monitoring orders and validating transactions. This system was developed using the PHP programming language with a bootstrap framework and MySQL database. System testing was carried out using the Black Box Testing method which shows that the Amuan Store sales system runs according to the design and does not show any errors or bugs. The development results show that this system is able to support the Amuan Store's needs in marketing products, recording transactions in a structured manner and increasing operational efficiency. The XP method also allows for system development, so that the system can continue to be updated according to market needs and dynamics. In this way, it is hoped that the sales information system for the Amuan Store will be an adaptive and responsive solution in supporting the sales management of the Amuan Store.